A probe to study the toxic interaction of tartrazine with bovine hemoglobin at the molecular level. (8th May 2013) - Li, Yating; Wei, Haoran; Liu, Rutao
ABSTRACT Tartrazine is an artificial azo dye commonly used in food products, but tartrazine in the environment is potentially harmful. The toxic interaction between tartrazine and bovine hemoglobin (BHb) was investigated using fluorescence, synchronous fluorescence, UV–vis absorption, circular dichroism (CD) and molecular modeling techniques under simulated physiological conditions. The fluorescence data showed that tartrazine can bind with BHb to form a complex. The binding process was a spontaneous molecular interaction, in which van der Waals' forces and hydrogen bonds played major roles. Molecular docking results showed that the hydrogen bonds exist between the oxygen atoms at position 31 of tartrazine and the nitrogen atom NZ7 on Lys99, and also between the oxygen atoms at position 15 of tartrazine and the nitrogen atom NZ7 on Lys104, Lys105. The results of UV–vis and CD spectra revealed that tartrazine led to conformational changes in BHb, including loosening of the skeleton structure and decreasing α helix in the secondary structure. The synchronous fluorescence experiment revealed that tartrazine binds into the hemoglobin central cavity, and this was verified using a molecular modeling study. Copyright © 2013 John Wiley & Sons, Ltd.